On the genealogy of the global health justice movement - Richard Parker (Taylor & Francis Group, 2023)
ABSTRACTIn the wake of the COVID-19 pandemic, it is clear that the struggle for global health justice must be our highest priority. To understand the challenges that such a priority faces, we must recognise that this struggle has a long history, and to analyse current challenges within this historical perspective. This commentary explores the gradual construction of the global health justice movement during different historical periods (tropical/colonial medicine, international health, and global health) in the history of approaches to health worldwide. It examines the changing relationship between the political economy of capitalism, colonialism, and racism. It analyses attempts to confront injustice through both human rights and social justice movements in seeking to address stigma and discrimination as well as poverty and social exclusion. It highlights emerging battlegrounds such as access to medical treatments and healthcare services as well as the ways in which private interests continue to undercut such efforts. But it also points to windows of opportunity for defending principles such as solidarity and social inclusion, for building advocacy/analysis alliances and toolkits to inform social movements, and possibilities to reconstruct global health 'governance' mechanisms and institutions in accord with the most basic principles of health justice.